Redox chemistry in the pigment eumelanin as a function of temperature using broadband dielectric spectroscopy - Bernard Mostert (RSC Advances, 2019)
Conductive biomolecular systems are investigated for their promise of new technologies. Onebiomolecular material that has garnered interest for device applications is eumelanin. Its unusualproperties have led to its incorporation in a wide set of platforms including transistor devices andbatteries. Much of eumelanin's conductive properties are due to a solid state redox comproportionationreaction. However, most of the work that has been done to demonstrate the role of the redox chemistryin eumelanin has been via control of eumelanin's hydration content with scant attention given totemperature dependent behavior. Here we demonstrate for the first time consistency between hydrationand temperature effects for the comproportionation conductivity model utilizing dielectric spectroscopy,heat capacity measurements, frequency scaling phenomena and recognizing that activation energies inthe range of ~0.5 eV correspond to proton dissociation events. Our results demonstrate thatbiomolecular conductivity models should account for temperature and hydration effects coherently.NOTE: Abstract is from RSC Advances, 2019, by Motovilov et al, under the creative commons licence CC BY-NC 3.0. No changes made to the abstract. Not used for commercial purposes.